Financial literacy on MSME export import decisions and the affecting individual and social factors - Farliana, Nina; Sakitri, Wijang; Utami, Sri; Widhiastuti, Ratieh; Rahmaningtyas, Wisudani (Publisher of Widyagama University of Malang (UWG Press), 2023)
This study aims to analyze financial literacy affecting export and import decisions, and to analyze what individual and social factors affecting the said financial literacy. The design of this research was clausal associative, with quantitative approach. The sample of this research was MSME actors in Central Java province who were successful or oriented towards carrying out export and import activities. The data collection techniques were questionnaires and documentation. This study used structural equation modeling with Lisrel 8.80 software. The data were analyzed with Confirmatory Factor Analysis. The results showed that there was a significant effect between individual ability on financial literacy and financial literacy on export and import decisions, while between social variables and financial literacy, there was not a significant effect. MSMEs had cooperative characteristics in running their business to complement each other's limitations and gain specific competitive advantages to compete in the global environment, especially export and import activities, so that they could contribute to the national economy. Suggestions for further research, the government should act as an aggregator or facilitator for sharing knowledge regarding financial literacy between MSMEs, MSMEs and academics, MSMEs and related communities, and MSMEs and national private parties.JEL ClassificationÂ F20; G53; L26